WYKORZYSTANIE METODY ANALIZY OKRESOWEJ (DURAC JI) DO OCENY RYZYKA KREDYTOWEGO - Wiśniewski, Marcin (Wydział Prawa i Administracji UAM, 2007)
Duration analysis is a method applied in interest rate risk management, especially in risk quantification. In the author’s opinion, this method may also be used to estimate credit risk. Every bank who grants a credit or investor investing in securities wants to be ensured about the credibility of the potential borrower or debtor, which may be impaired by already existing debts. Therefore, when estimating credibility, one must measure the debt burden of the potential borrower. The duration method may be considered as a tool to quantify that burden. The duration ratio value may indicate the length of the average period in which the loan will be repaid. The weights used in this ratio calculation would be the discounted values of the principal and interest repayments expressed as a percentage of their total. With this ratio, different potential borrowers could be compared in respect of selected factors. A concept of a duration method and its current as well as potential application in credit risk management has been presented.